National Geographic extreme weather survival guide : understand, prepare, survive, recover - Kostigen, Thomas (National Geographic, 2014)
Accompanied by first-hand accounts from survivors, helps readers prepare for and respond to emergencies and survive the worst-case scenarios during such extreme weather events as hurricanes, floods, wildfires, and tornadoes.